1985
DOI: 10.1093/bja/57.8.732
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Ici 35868, Etomidate and Methohexitone for Day-Case Anaesthesia

Abstract: ICI 35868 is a substituted phenol (2-6, diisopropyl phenol) which has been shown to have anaesthetic properties. It is rapidly acting (7J approximately 55 min), and is completely metabolized, mainly by conjugation with glucuronic acid. There is minimal cumulation, more than 90 % of the dose being recovered in the urine (as metabolites) within 48 h.This study was designed to compare the efficacy and side-effects of di-isopropyl phenol, etomidate and methohexitone, when used for day-case anaesthesia. PATIENTS AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…That the incidence and duration of apnoea were almost identical for both drugs reflects on the relatively heavy opioid premedication. It is difficult to compare these findings with adult studies because the reported incidence of apnoea varies from 12 to 100% (Nightingale et al, 1984;Wells, 1985). Fahy, van Mourik and Utting (1985), using a technique similar to that utilized in this study, reported a higher incidence of apnoea with bodi thiopentone and propofol than we have found.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…That the incidence and duration of apnoea were almost identical for both drugs reflects on the relatively heavy opioid premedication. It is difficult to compare these findings with adult studies because the reported incidence of apnoea varies from 12 to 100% (Nightingale et al, 1984;Wells, 1985). Fahy, van Mourik and Utting (1985), using a technique similar to that utilized in this study, reported a higher incidence of apnoea with bodi thiopentone and propofol than we have found.…”
Section: Discussioncontrasting
confidence: 48%
“…Using the emulsion formulation, we have found a 24% incidence of pain using antecubital fossa veins, compared with 10% with thiopentone. Although none were considered to be severe, these findings contrast markedly with die low incidence of pain diat was found in adults using antecubital fossa veins and the emulsion formulation of propofol (2.5-12%), or thiopentone (0%) (Kawar and Dundee, 1982;McCulloch and Lees, 1985;Wells, 1985). The incidence of pain on injection in adults is higher when the smaller veins on the dorsum of the hand are used (Kawar and Dundee, 1982;McCulloch and Lees, 1985;Mackenzie and Grant, 1985).…”
Section: Discussionmentioning
confidence: 82%
“…With the new emulsion formulation the incidence of pain on injection is lower but still occurs in 30-50:/, of patients when injected into veins in the dorsum of the hand (10, 11). If, however, veins in the forearm or in the antecubital Sossa are used, the incidence of pain can be substantially reduced (to about 10%) (12).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of propofol used in conjunction with other induction agents, suggested that, in man, fewer and less significant side effects were seen than with methohexitone or etomidate. It compared favourably with thiopentone (Wells 1985;McCollum and Dundee 1986). A multicentre study of the drug (Sanderson 1988), performed after its launch in the open market, found that about 8.4 per cent of patients had abnormal reactions following its administration.…”
Section: Introductionmentioning
confidence: 99%